The Influence of Social Media Advertising, Word of Mouth, and Owner Personal Branding on Consumer Trust in Culinary MSMEs in Cirebon City. - Yasser Muhamad; Rudianto Rudianto; Siska Ernawati (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
This study addresses the need of culinary micro, small, and medium enterprises to build consumer trust within a competitive digital marketplace. The objective is to determine the extent to which social media advertising, word of mouth, and owner personal branding affect consumer trust. A quantitative explanatory approach was employed with 120 consumers of culinary MSMEs in Cirebon who actively access social media. Data were collected via a Likert‑scale questionnaire and analyzed using multiple linear regression following validity, reliability, and classical assumption tests. The results indicate that all three predictors exert positive and significant effects on consumer trust, both partially and simultaneously, with the model explaining 58 percent of the variance. These findings highlight that transparent and consistent advertising, credible consumer reviews, and the owner’s authenticity and competence provide complementary trust signals. The study concludes that an integrated orchestration of paid, earned, and owned channels is essential to strengthen consumer trust in culinary MSMEs.